2004
DOI: 10.1889/1.1833136
|View full text |Cite
|
Sign up to set email alerts
|

59.5L: Late‐News Paper: A 68‐inch SVGA 4×4 Tiled Display

Abstract: In this paper, we describe recent advances in the production and performance of a seamless tiled display technology. A new automated method to produce arrays of optical light guides has been implemented in the development of a 68‐inch 16‐tile SVGA (800×600) display.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…As an alternative to the refractive optics element, a waveguide optics element was constructed by using molded optical fiber or fibers array [2,3]. The study showed impressive advance in viewing angle characteristics.…”
Section: Figurementioning
confidence: 99%
“…As an alternative to the refractive optics element, a waveguide optics element was constructed by using molded optical fiber or fibers array [2,3]. The study showed impressive advance in viewing angle characteristics.…”
Section: Figurementioning
confidence: 99%
“…Special needs are increased in information display about size, luminance, image sticking, and lifetime. In recent years, numerous studies have attempted to find the methods of large size and high luminance [2][3][4][5]. The use of RGBW color subpixels has been proposed because its optical efficiency is at least 50% higher than that of the RGB system [4].…”
Section: Figure 1 Market Forecast By Categorymentioning
confidence: 99%
“…Typically tile displays are made by arranging multiple panels in the same plane as close as possible. Some advanced LCD tiled displays adopt optical components which control light path ways to eliminate boundary seam areas between two adjacent LCD panels [1].…”
Section: Introductionmentioning
confidence: 99%